Optimization of the MBKM Role in Enhancing Student Career Capacity Through Learning Experiences - Rosi, Fathor; Nu'man, Agus (International Journal of Instructional Technology, 2024)
This research focuses on improving the accessibility of the Merdeka Belajar Kampus Merdeka (MBKM) program and its impact on enhancing students' career capacity through inclusive and diverse learning experiences. The main objective of this study is to identify the role of scholarships and the flexibility of the MBKM program in expanding access for students with financial limitations and how this affects their job readiness. The research method used is descriptive qualitative, with data collected through in-depth interviews with students participating in the MBKM program and analysis of documents related to MBKM policies. The findings indicate that strengthening the synergy between higher education institutions and industries, improving the quality of learning through practical experiences, diversifying the MBKM program, and significantly enhancing the accessibility of the MBKM program increases student participation, especially from lower-middle economic groups, contributing to the development of practical skills and their readiness to face the job market. The implications of this research underscore the importance of designing more inclusive and adaptive higher education programs to create competent graduates ready to compete in the global job market. This study also recommends the need for more comprehensive further research to accommodate variations in gender, age, and broader methods to understand the impact of educational accessibility on diverse student groups.